The epidemic of human papillomavirus virus-related oropharyngeal cancer: current controversies and future questions - Allen M. Chen (Infectious Agents and Cancer)
Abstract The incidence of human papillomavirus (HPV) associated oropharyngeal cancer has increased to epidemic-like proportions in the United States and other industrialized nations. While significant progress has been made in the understanding of this disease with respect to its underlying biology and clinical behavior, numerous questions persist regarding treatment. It is now firmly established that patients with HPV-positive oropharyngeal cancer have a significantly improved prognosis as a result of their exquisite radiosensitivity compared to their HPV-negative counterparts and thus can be targeted with de-escalated approaches using reduced doses of radiation and/or chemotherapy. The fundamental goal of de-escalation is to maintain the high cure and survival rates associated with traditional approaches while reducing the incidence of both short- and long-term toxicity. Although the exact reason for the improved radiosensitivity of HPV-positive oropharyngeal carcinoma is unclear, prospective studies have now been published demonstrating that de-escalated radiation can successfully maintain the high rates of cure and preserve quality of life for appropriately selected patients with this disease. However, the selection criteria and specific means for de-escalation remain uncertain, and paradigms continue to evolve. Given that HPV-positive oropharyngeal cancer is increasingly recognized as a public health problem, the search for answers to many of these provocative questions has important societal implications and is the subject of this review.